2017
DOI: 10.3389/fonc.2017.00208
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Drones to Target Lung Cancer with Radiosensitizers and Cannabinoids

Abstract: Nanotechnology has opened up a new, previously unimaginable world in cancer diagnosis and therapy, leading to the emergence of cancer nanomedicine and nanoparticle-aided radiotherapy. Smart nanomaterials (nanoparticle drones) can now be constructed with capability to precisely target cancer cells and be remotely activated with radiation to emit micrometer-range missile-like electrons to destroy the tumor cells. These nanoparticle drones can also be programmed to deliver therapeutic payloads to tumor sites to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…In the traditional intravenous routes (injection or infusion) of delivery of NPs, the NPs have to navigate through physiological barriers before some portion of the NPs reaches the tumor site [1]. Studies have shown that of the NPs delivered (including targeted drug and nanoparticles) via systemic routes, only a portion of the administered dosage reaches the target tumor site, even with the enhanced permeability and retention (EPR) effect [3,57,64,65], whereas the remainder of the dose remains in systemic circulation, leading to systemic toxicity [57].…”
Section: Delivery Of Nbr Via Intravenous Routesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the traditional intravenous routes (injection or infusion) of delivery of NPs, the NPs have to navigate through physiological barriers before some portion of the NPs reaches the tumor site [1]. Studies have shown that of the NPs delivered (including targeted drug and nanoparticles) via systemic routes, only a portion of the administered dosage reaches the target tumor site, even with the enhanced permeability and retention (EPR) effect [3,57,64,65], whereas the remainder of the dose remains in systemic circulation, leading to systemic toxicity [57].…”
Section: Delivery Of Nbr Via Intravenous Routesmentioning
confidence: 99%
“…However, radiation boosting can substantially increase the survival rate for patients with lung cancers, but is restricted by healthy tissue toxicity due to the respiratory motion [68,[70][71][72]. The proposed treatment strategy to overcoming the limitations is to increase the dose to the tumor volume, while carefully sparing the surrounding normal lung tissue by increasing local radiosensitization via inhalation nanoparticles, as seen in Figure 1B, and decreasing the dose to balance complications and cancer cure [1,68]. Combined chemoradiotherapy is the best strategy for boosting the radiation dose to the tumor.…”
Section: Delivery Of Nbrs Via Inhalationmentioning
confidence: 99%
See 3 more Smart Citations